2013
DOI: 10.3174/ajnr.a3667
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Consistency of Pituitary Macroadenomas: Predictive Analysis on the Basis of Imaging Features with Contrast-Enhanced 3D FIESTA at 3T

Abstract: BACKGROUND AND PURPOSE:Preoperative evaluation of pituitary macroadenoma tumor consistency is important for neurosurgery. Thus, we aimed to retrospectively assess the role of contrast-enhanced FIESTA in predicting the tumor consistency of pituitary macroadenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 17 publications
3
65
0
Order By: Relevance
“…In transsphenoidal surgery for such firm pituitary adenomas, excessive maneuvers increase morbidity and mortality related to visual disturbance, panhypophysis, and intraand extracapsular hemorrhage. Although previous studies have and contrast-enhanced 3D FIESTA, 3 these methods did not directly measure the shear stiffness of pituitary adenomas. To the best of our knowledge, our study is the first to demonstrate the shear stiffness of pituitary adenomas by using MRE.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In transsphenoidal surgery for such firm pituitary adenomas, excessive maneuvers increase morbidity and mortality related to visual disturbance, panhypophysis, and intraand extracapsular hemorrhage. Although previous studies have and contrast-enhanced 3D FIESTA, 3 these methods did not directly measure the shear stiffness of pituitary adenomas. To the best of our knowledge, our study is the first to demonstrate the shear stiffness of pituitary adenomas by using MRE.…”
Section: Discussionmentioning
confidence: 97%
“…Although conventional MR imaging and some other MR imaging sequences have been reported capable of predicting intracranial tumor consistency or fibrosis, they have not been used to directly assess the viscoelastic properties of tumors. [1][2][3] MR elastography (MRE) is an emerging technology enabling the noninvasive assessment of the viscoelastic properties of tissues in vivo. 4,5 MRE uses continuous shear waves generated by an extracorporeal mechanical wave driver, imaging the propagating shear waves with a phase-contrast MR image, and processing the wave images with an inversion algorithm to obtain a quantitative cross-sectional image of the shear stiffness map known as an elastogram.…”
mentioning
confidence: 99%
“…Yamamoto et al 27 suggested that tumour consistency of pituitary macroadenomas could be predicted accurately by contrast-enhanced 3D FIESTA than do conventional MRI imaging techniques such as contrast-enhanced T1-weighted and T2-weighted MRI imaging. Nevertheless, in Singapore, contrast-enhanced 3D FIESTA is not routinely used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…While Yamamoto et al 27 excluded patients who underwent prior surgery or any other forms of prior medical therapy for the pituitary macroadenomas, assessing the consistency of pituitary macroadenomas which have been initially treated with dopaminergic agents through contrast-enhanced 3D FIESTA is certainly a prospect to be further explored in the future. This could potentially change neurosurgical practice and benefits could be accrued in terms of better planning of the surgery from the neurosurgeons’ end, and also better preparation of the patient for a possibility of a second surgery, should the tumour be predicted to be fibrous preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…However, approximately 10% of PMA are firm which alters surgical technique and may impact surgical outcome and approach [1,2]. While various magnetic resonance imaging (MRI) based methods have been investigated to determine the consistency of pituitary macroadenomas (PMA), none of the methods have proven capable of characterizing tumor stiffness [3-6]. These methods, including measurement of standard T1 and T2 signal and features of contrast enhancement and diffusion, are based on static imaging characteristics and cannot directly measure stiffness.…”
Section: Introductionmentioning
confidence: 99%